Coalition government and party mandate : How coalition agreements constrain ministerial action - Moury, Catherine (Routledge research on social and political elites., 2013)
Which kind of decisions are passed by Cabinet in coalition governments? What motivates ministerial action? How much leeway do coalition parties give their governmental representatives? This book focuses on a comparative study of ministerial behaviour in Germany, Belgium, Italy and the Netherlands. It discredits the assumption that ministers are 'policy dictators' in their spheres of competence, and demonstrates that ministers are consistently and extensively constrained when deciding on policies. The first book in a new series at the forefront of research on social and political elit.